Ostracism in the era of COVID-19: Intrapersonal, interpersonal, and intergroup perspectives - Theofilos Gkinopoulos; Galanaki, Evangelia P. (In M. H. Bowker & A. Buzby (Eds.). Getting lost: Reflections on psychopolitical isolation and withdrawal, 2025)
COVID-19 pandemic had a profound negative impact on people’s personal and social life. In this chapter, after some conceptual clarifications, we provide insights into the effects of ostracism on people’s well-being as individuals, partners, and group members. Specifically, we explore (a) individual- and personality-based risk factors of ostracism (intrapersonal level); (b) deprivation of social touch, disruption of empathy and social stigmatization in interpersonal relations (interpersonal level); and (c) disruption of social identity, social stigmatization and rise in prejudiced, discriminatory, and xenophobic tendencies within groups (intergroup level). The contribution of this chapter lies in proposing an interplay among intrapersonal, interpersonal, and intergroup dimensions of identity, that is, a multi-level conceptualization of ostracism during the covidian era. By integrating theoretical arguments and research findings, we support the view that personal identity commitment and identification with social groups have similar roots, both based on the individual’s need to formulate meaningful connections to the world and, thus, cope with as well as prevent ostracism. The implications of the interplay between personal and social identity for the measurement of ostracism are also discussed. Next, strategies for tackling ostracism during the pandemic or similar widespread crises are proposed. Finally, avenues for future research are suggested.